2022
DOI: 10.3390/ijerph19010487
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Body Composition and Physical Fitness and the Effect of Exercise According to the Level of Childhood Obesity Using the MGPA Model

Abstract: Childhood obesity can lead to adulthood obesity with adverse effects. Since body composition and physical fitness differ depending on the obesity degree, a systemic analysis could help classify that degree. We used three study designs based on the obesity degree (body mass index [BMI] as a reference) for our objectives. First, we identified the relationship between body composition and physical fitness. Second, we determined the effects of exercise on body composition and physical fitness. Third, we performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
5
3
0
1
Order By: Relevance
“…As a result, post-hoc analysis showed that the overweight group demonstrated dramatic difference in weight, BMI, and %BF compared with the other groups, while there was no signi cant difference in the height among all three groups. Our ndings are consistent with those of previous studies in this regard [25]. From our ndings, we observed that the 11-week physical exercise program had the greatest positive effect in children with overweight, followed by obese children.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As a result, post-hoc analysis showed that the overweight group demonstrated dramatic difference in weight, BMI, and %BF compared with the other groups, while there was no signi cant difference in the height among all three groups. Our ndings are consistent with those of previous studies in this regard [25]. From our ndings, we observed that the 11-week physical exercise program had the greatest positive effect in children with overweight, followed by obese children.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we aimed at demonstrating the effect of physical exercise on physical tness and executive function in children with overweight or obesity. On the basis of previous literature [24][25], the general hypothesis was that 11-weeks physical exercise program improves physical tness and executive function in children with overweight or obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings corroborated with those of several studies suggesting that physical fitness may play a leading role in the prevention of obesity in children and adolescents ( 20 , 46 – 48 ). Nevertheless, our results differ from those of Chen et al ( 20 ) and Xu et al ( 47 ) in the curved relationship between fitness and BMI observed by these authors, suggesting that the relationships between BMI and fitness among college students are nonlinear.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, our conclusion was later substantiated by Lee’s study. Consistent with a previous study, Lee’s article pointed out that 16 weeks of physical exercise interventions caused the greatest change in PF, which was demonstrated by the significant increase in PF variables, such as muscular strength, flexibility, muscular endurance, and balance showed a significant increase [ 32 ]. The latest research by Ortega et al further investigated the effects of physical exercise on cardiorespiratory fitness among children who are overweight or obese.…”
Section: Discussionsupporting
confidence: 77%